Comparative Study of Solvent Extraction of Uranium with Alamine 336 and Aliquat 336: Application to the Uranium-Bearing Solutions of Niger Republic - Abdoul-Rachid, Chaibou Yacouba; Salmana, Laouali Ibahim; Adamou, Zanguina; Ibrahim, Natatou; Ibrahim, Mamane (European Scientific Journal, ESJ, 2018)
This study focuses on the liquid-liquid extraction of uranium by anionic extractants of Alamine 336 and Aliquat 336. The objective of this study is to determine the parameters allowing the optimization of the extraction percentage of uranium, and other metals such as molybdenum, zirconium and vanadium. The extraction kinetics of uranium is achieved in 2 minutes. Sulfuric acid solutions are the media per excellence when using Alamine 336 as extractant. However,with Aliquat 336, it is orthophosphoric acid. Uranium is extracted at 99% in a single contact from the ratio: organic phase over aqueous phase (O/A) equals 1. The extraction of uranium with Alamine 336 depends on the initial pH of the aqueous phase as well as the Alamine 336 concentration. Alamine 336 tends to release the uranium and the extracted zirconium until the 3 rd contact to the benefit of the molybdenum due to the natural occurrence of 𝐶𝑙−,𝑁𝑂3 − and 𝐹 − ions in the uranium-bearing solutions which have the tendency of breaking the anion complexes. Vanadium, which is not extracted by Alamine 336 and Aliquat 336, can, in the hydrodynamic conditions of this work, be extracted by increasing the redox potential to 800 mV and pH ≥ 1.